Transformasi Studi Hadis Tematik di Era Digital: Antara Tradisi Klasik dan Teknologi Modern - Muhammad Ash Shaff Muzakki; Apit Hidayat; Zaenal Abidin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This article explains that the transformation of thematic hadith studies in the digital age marks a major shift in the way Muslims access and understand hadith sources. This study aims to outline the changes in the approach of thematic hadith studies from classical tradition to digital practice, as well as to examine the challenges and opportunities that arise from these changes. The study used a qualitative approach with a desk study method, analyzing primary and secondary references that discuss thematic hadith methodology in various periods. The results of the study show that the classical approach emphasizes sanad validity, matan criticism, and strong contextual linkages, while the digital approach is more prominent in aspects of access efficiency and outreach. However, without a strong methodological foundation, digitization is prone to bias and simplification of hadith meanings. Therefore, an integrative approach is needed that combines the scientific rigor of the classical tradition with the convenience offered by modern technology. This study affirms the importance of maintaining the integrity of thematic hadith studies to remain epistemologically sound amidst the accelerating digitalization.